The pedagogue's reflections on the need to notice the ethical conditions of the changes necessary in the teaching attitudes in the 21st century Part I (From national education to cross-border education open to equal opportunities) - Mirosław Mieczysław Wójcik (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
In the article, the author attempts to analyze the contemporary conditions for the necessary changes in teachers' attitudes. He perceives the philosophical reflection in the direction of ethics as the basis for drawing conclusions on the optimal education and shaping and professional functioning of people responsible for the education of the young generation. In the reflectiveness of the educational environment, the author also perceives the chance to understand the ethical conditions of changes in the contemporary profiles of teachers, which are forced by new demographic and socio-cultural phenomena in Europe and in the world. The article is in line with the search for a thoroughly modern paradigm of personality of educators in the XXI century.